Descriptive Use of Flashcard Media in Elementary School Students' Beginning Reading: Literature Review - orine paembonan; roswita; yosalia tuntun; aulia salsabila (Journal of Creative Power and Ambition (JCPA), 2026)
A child's literacy success in subsequent levels of education depends heavily on the strength of the reading foundation they build from an early age. The reality on the ground shows a different picture: many early elementary school students still struggle with letter recognition, syllable connection, and even fluently constructing simple sentences. Flashcards are one of the media options often used by teachers to bridge this gap. This article aims to provide an overview of the use of flashcards in early reading instruction in elementary schools, drawing on various published research findings. The paper utilizes a descriptive-qualitative literature review approach, drawing from national journal articles from 2018 to 2025 that address flashcards in the context of early reading. The analysis process involved data reduction, data presentation, and drawing conclusions. The findings demonstrate a fairly consistent pattern: flashcard use is often associated with increased student ability to recognize letters, combine syllables, read fluently, and pronounce words correctly. The attractive visual appearance and practicality of this medium are key drivers of its success, although on the other hand, obstacles remain, such as limited class time, a limited number of flashcards, and some teachers' reluctance to abandon conventional teaching practices. This paper recommends that flashcards continue to be considered as a simple yet applicable medium for teaching early reading for elementary school teachers.